2019
DOI: 10.1177/2332858419870489
|View full text |Cite
|
Sign up to set email alerts
|

Does the Flipped Classroom Improve Student Learning and Satisfaction? A Systematic Review and Meta-Analysis

Abstract: We searched and meta-analyzed studies comparing flipped classroom teaching with traditional, lecture-based teaching to evaluate the evidence for the flipped classroom’s influence on continuous-learning measures, pass/fail rates, and student evaluations of teaching. Eight electronic reference databases were searched to retrieve relevant studies. Our results indicate a small effect in favor of the flipped classroom on learning (Hedges’ g = 0.35, 95% confidence interval [CI] [0.31, 0.40], k = 272). However, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
143
4
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(173 citation statements)
references
References 81 publications
(147 reference statements)
11
143
4
15
Order By: Relevance
“…The study found that flipped classrooms had a medium effect on academic outcomes; the average scores of students in flipped classrooms were 0.35 standard deviations above the average scores of students in traditional, lecture-based classrooms. It also confirmed the results of previous, related studies (e.g., ES = 0.36 [3]; ES = 0.35 [9]; ES = 0.53 [77]; ES = 0.21 [78]). In short, its findings demonstrate that flipped classrooms can improve college students' academic outcomes in various ways, could provide an effective way to inculcate essential 21st-century skills in students [79], and may assist students with special educational needs in performing better than they would in traditional, lecture-based classrooms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study found that flipped classrooms had a medium effect on academic outcomes; the average scores of students in flipped classrooms were 0.35 standard deviations above the average scores of students in traditional, lecture-based classrooms. It also confirmed the results of previous, related studies (e.g., ES = 0.36 [3]; ES = 0.35 [9]; ES = 0.53 [77]; ES = 0.21 [78]). In short, its findings demonstrate that flipped classrooms can improve college students' academic outcomes in various ways, could provide an effective way to inculcate essential 21st-century skills in students [79], and may assist students with special educational needs in performing better than they would in traditional, lecture-based classrooms.…”
Section: Discussionsupporting
confidence: 91%
“…This study conducted a meta-analysis of the effects of flipped classrooms on students' cognitive, affective, and interpersonal outcomes in higher education. It extends the discussions and findings from recent meta-analyses that found that flipped classrooms had a significant effect on students' cognitive outcomes in higher education: for example, by improving their test scores, grade, knowledge, skills, and self-directed learning (e.g., [9,76,77]). This study expands the evidence for flipped classroom effectiveness in improving college students' academic outcomes as compared to traditional, lecture-based classrooms.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In these studies, student in the intervention group were given free access to a website/app immediately after the traditional classroom teaching nished. An aspect and explanation regarding the signi cant differences between m-learning (app) and traditional learning resources and their context (books, articles and classroom teaching or laboratories) in learning practical skills is that the mobile learning activities can be designed in alignment with the learning outcomes and the assessment form (48). Another explanation of the results showing no signi cant effect on knowledge acquisition is that, if the app is mainly designed to learn practical skills, then the knowledge aspect might not be supported or facilitated as a learning outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches have been proposed for a smooth transition from lecture-based knowledge received in classrooms to practical skills used for research purposes. Classroom lectures in which learning materials previously explored for students and they work on are called a flipped classroom [3], [4]. In a blended learning style, online digital learning media is used with traditional classroom methods in combination [5]- [8].…”
Section: Introductionmentioning
confidence: 99%